Retail Sugar From One Zambian Community Does Not Meet Statutory Requirements for Vitamin A Fortification - Greene, MD; Kabaghe, G; Musonda, M; Palmer, AC (SAGE Publications, 2017)
Industrial food fortification is a major strategy to improve dietary micronutrient intakes and prevent deficiencies. Zambia introduced mandatory sugar fortification with vitamin A, at a target of 10 mg/kg, in 1998. Representative surveys conducted since that time do not support marked improvement in vitamin A status.To describe vitamin A concentrations in retail sugar, as well as vendor practices, perceptions of fortified foods, and sugar use practices.We conducted a census of sugar vendors in one Zambian community, capturing information on vendors, available brands and packaging options, and storage conditions. We purchased all brands and package types of sugar available at each vendor. In a 15% subsample, we conducted semi-structured interviews with vendor–consumer pairs. We tested 50% of sugar samples at random for vitamin A using an iCheck portable fluorimeter.The distribution of vitamin A in sugar in market samples was highly skewed, with a median of 3.1 mg/kg (25th-75th percentiles: 1.8-5.5) and a range from 0.2 to 29.9 mg/kg. Only 11.3% of samples met the 10 mg/kg statutory requirement. Sugar was primarily repackaged and sold in small quantities, with rapid turnover of stocks. Perceptions of fortification by vendors and consumers were generally positive.Vitamin A in fortified sugar fell well below statutory requirements. Our data point to challenges at regional depot and/or poor adherence to fortification standards at the factory level. A renewed commitment to monitoring and enforcement will be required for Zambia to benefit from a food fortification strategy.